Analisis Kredibilitas Non Endorse Youtuber Serta Pengaruhnya Pada Niat Pembelian - Diddo Adding Adove; Mochammad Farid Afandi; Fajar Destari (Asosiasi Peneliti Manajemen Adat Indonesia, 2022)
Influencer marketing has grown rapidly nowadays on social media platforms, one of which is YouTube. Youtubers who are not in-house with brand or non-endorsed YouTubers have more trustworthy information in providing reviews regarding a product. Based on this, this study focuses on non-endorse YouTubers by proposing a source credibility model in the form of expertise, trustworthiness and homophilia on information accessibility and consumer purchase intentions. The survey was conducted using a questionnaire which was then distributed to respondents via social media. Furthermore, 423 data were obtained from respondents who were then evaluated based on certain criteria. A total of 380 valid data obtained after conforming to the research criteria from all the data obtained. Valid data are then analyzed using PLS analysis with the help of the SmartPls 3 application. The findings of this study indicate that the expertise, trust and homophilia of non-endorsed YouTubers have a significant effect on the credibility of information and purchase intentions. In addition, the credibility of information also significantly affects purchase intentions.